2005
DOI: 10.1158/1078-0432.ccr-04-2277
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Matrix Metalloproteinase-1 Is Prognostic in Head and Neck Squamous Cell Carcinoma: Comparison of the Circulating and Tissue Immunoreactive Protein

Abstract: Purpose:Tissue inhibitors of metalloproteinases (TIMP) are capable of inhibiting the matrix metalloproteinases, but they also possess other biological functions. Little is known about the role of TIMP-1in the progression and spreading of cancer cells among patients with head and neck squamous cell carcinoma (HNSCC). In this study, the pretreatment serum levels of TIMP-1or the overexpression of TIMP-1 immunoreactive protein in the primary tumor was correlated to the clinical course in patients with HNSCC. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
2
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
6
29
2
8
Order By: Relevance
“…In patients with head and neck squamous cell cancer. the level of TIMP-1 in tissues and serum are associated with unfavorable prognosis (Ruokolainen et al, 2005). Our present study demonstrates that levels of TIMP-1 are significantly elevated in plasma (by 1.7-and 1.8-fold) in patients with stage IV and III UBC, respectively, compared to controls.…”
Section: Discussionsupporting
confidence: 47%
“…In patients with head and neck squamous cell cancer. the level of TIMP-1 in tissues and serum are associated with unfavorable prognosis (Ruokolainen et al, 2005). Our present study demonstrates that levels of TIMP-1 are significantly elevated in plasma (by 1.7-and 1.8-fold) in patients with stage IV and III UBC, respectively, compared to controls.…”
Section: Discussionsupporting
confidence: 47%
“…A study by Li et al (28) that investigated the expression of FGF-BP in HNSCC in 35 primary (8 from the larynx, 11 from the oral cavity, 4 from the pharynx, 5 from the neck, 3 from the nasal cavity and 4 from the face) and 8 metastatic specimens, as well as 7 control tissues, identified an increased expression of FGF-BP in primary and metastatic tissue specimens compared to adjacent control tissue and concluded that an increased FGF-BP expression is associated with angiogenesis by measuring microvessel count. Ruokolainen et al (12) observed that pre-treatment serum levels of TIMP-1 (n=68) and TIMP-1 in the tumour tissue (n=74) were positively correlated with the size of the tumour. However, in accordance with the present findings, no positive correlation was observed between tissue TIMP-1 positivity or serum TIMP-1 levels and disease stage or tumour grade.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (11) investigated the expression of angiogenic factors in tumour tissue, HNSCC cell lines and serum, and established that IL-8, VEGF and GM-CSF produced by HNSCC are consistent with the pathology of the neoplasm. In addition, Ruokolainen et al (12) reported circulating and tissue TIMP-1 to be associated with a shortened cause-specific and relapse-free survival of HNSCC patients. In accordance with the present study, a previous study suggested a role for angiogenin in HNSCC, demonstrating an increased expression measured by immunohistochemistry, in situ hybridization, or serum concentration in numerous malignancies, including breast, cervical, gastric, hepatic, renal, prostate, pancreatic, endometrial and colorectal cancer, leukemia, lymphoma, melanoma and osteosarcoma (13).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue inhibitors of matrix metalloproteinases (TIMPs) are molecules, that are able to inhibit the activities of all MMPs, but they also have several other functions independent of the MMP inhibition, such as effects on angiogenesis, growth, and apoptosis [5]. MMP-2, MMP-9, TIMP-1, and TIMP-2 have been demonstrated to exhibit prognostic value in several solid cancers [6][7][8][9][10]. It has also been reported both by us and other authors, that high MMP-9 protein expression is an indicator for an adverse prognosis in patients with DLBCL treated mainly with CHOP-type chemotherapy [11,12].…”
Section: Introductionmentioning
confidence: 99%